(untitled) (Research, Society and Development, 2021)
Objective: to identify the care provided to the newborn and guidelines for postpartum women in rooming-in. Methods: descriptive, cross-sectional study, carried out with 290 mothers in two public maternity hospitals, linked to the Rede Mãe Paranaense Program, from August to December 2017. The variables were analyzed descriptively, considering simple frequency and percentage. Results: administration of vaccine against Hepatitis B, administration of vitamin K, newborn and heart tests were performed in 100% of newborns, from both maternity hospitals. Guidance on the advantages of breastfeeding, strategies to help breastfeeding, not using pacifiers/bottles, support when performing first care with the baby are actions that need greater engagement by the multidisciplinary team, as despite being carried out, they are still it does not reach all puerperal women. Conclusion: Newborn care such as administration of vitamin K, carrying out neonatal screening tests are already practices performed almost entirely in the studied maternity hospitals. However, with regard to support and guidance for newborn hygiene and breastfeeding, despite being consolidated, they still have some weaknesses.